Pengukuran Faktor yang Berpengaruh Terhadap Kualitas Hidup Penderita HIV/AIDS Pada Ibu Rumah Tangga - Siti Patimah (Citra Delima Scientific journal of Citra Internasional Institute, 2020)
Quality of life is a state where one gets satisfaction and enjoyment in everyday life. Quality of life is related to physical health and mental health which means if a person healthy physically and mentally then the person will achieve satisfaction in his life. The purpose of this research is to know the direct and indirect influence of health promotion of social environment, the role of health officer and the role of husband to the quality of life of HIV / AIDS sufferers in housewife at Yayasan Pelita Ilmu in 2017. This research uses cross sectional method with 70 samples respondents. Analytical methods used are Structural Equation Model (SEM) using Smart PLS2.0 and SPSS 18. The results of this study indicate the direct and indirect influence between health promotion variables, social environment, the role of health workers and husband role, to the quality of life of HIV / AIDS in housewives by 76.8%. The quality of life variable is directly influenced by several variables, including health promotion (12,14%), social environment (23,83%), health officer role (30,31%), and husband role (10,50%). Indirect effect of 1.51%. Pelita Ilmu Foundation counseling officers to provide support to HIV / AIDS sufferers in housewives by increasing the role of health workers to create HIV / AIDS sufferers in housewives with high quality of life.